PWE-063 Local experience of using tacrolimus as rescue therapy in resistant ibd. (22nd June 2015) - Lithgo, K; Price, T; Johnson, MW
Abstract : Introduction: Tacrolimus is a macrolide immunosuppressant. By inhibiting the transcription of interleukins (ILs) such as IL-2, tumour necrosis factor-α (TNF) and interferon-gamma, it exerts a powerful and selective suppression of T-cell function. Oral Tacrolimus has been used in patients with refractory ulcerative colitis, but its role in Crohn's disease has not yet been determined, especially when compared with alternative approaches such as anti TNFs. 1 We reviewed the clinical outcomes of a small but growing cohort of resistant IBD patients where Tacrolimus was started as rescue therapy. Method: The National IBD Registry was used to identify all IBD patients at the Luton and Dunstable University Hospital presently being treated on Tacrolimus. A retrospective review of these patients was then performed using data held on our National IBD Registry, Evolve (in-house hospital electronic records system) and ICE (hospital results system). A comparison was made of the data collected pre and post Tacrolimus therapy e.g. ESR, CRP, faecal calprotectin, Harvey Bradshaw Index (HBI) for Crohn's patients and modified UC Disease Activity Index (UCDAI) for ulcerative colitis patients. Results: The Luton and Dunstable University Hospital IBD Registry and Patient Management System now contains the clinical details of 3002 IBD patients. Of these a total of 10 patients had been started on Tacrolimus, 2 had Crohn's and 8 had ulcerative colitis (3 Pan UC, 1 left sided UC and 4 distal UC). These patients had been started on Tacrolimus for a range of reasons including; failure of a range of standard therapies, multiple drug sensitivities, patients refusing biological therapy, failure of biological therapy, biological funding issues, steroid dependancy, steroid contraindications and refusing admission for IV steroids. All patients improved on Tacrolimus, with reductions seen in the average HBI from 7.5 to 4.5, and in the average mUCDAI scores from 7.9 to 3.5. A decrease was also seen with the average CRP pre and post Tacrolimus therapy decreasing from 24.4 to 9.7, and with the ESRs from 30.2 to 7.8. No adverse reactions have been experienced to date. Conclusion: Our results suggest that Tacrolimus is a highly effective immunomodulator therapy, and a useful addition to the IBD therapeutic armoury, particularly in those with difficult or resistant UC or Crohn's disease. We have been impressed with its speed of action and ease of dose adjustment. Further studies are required to assess its longterm safety profile and use in Crohn's disease. Disclosure of interest: None Declared. Reference: Landy J, Wahed M, Peake ST, Hussein M, Ng SC, Lindsay JO, Hart AL. Oral tacrolimus as maintenance therapy for refractory ulcerative colitis-an analysis of outcomes in two London tertiary centres. J Crohns Colitis . 2013;7 (11):e516–21. doi: 10.1016/j.crohns.2013.03.008. Epub 2013 Apr 25